PKM KELOMPOK IBU MENYUSUI DI POSYANDU MELATI DESA BUKIT KRATAI WILAYAH KERJA UPT BLUD PUSKESMAS RUMBIO KABUPATEN KAMPAR - Nislawaty Nislawaty; Syukrianti Syahda (COVIT (Community Service of Health), 2021)
Breastfeeding is a very useful activity, not only for mothers but also for children. For infants and toddlers, breast milk is the best source of nutrition and has proven its efficacy in saving lives. Breast milk helps protect children from various diseases. Some breastfeeding mothers experience problems in giving breast milk to their babies, these problems include there are still mothers who complain of discomfort in breastfeeding so that it causes sore nipples and the amount of breast milk is decreasing. Education for breastfeeding mothers is very necessary so that mothers can comfortably give breast milk to their babies without feeling difficulties and worries about the quality of breast milk that will be enjoyed by their babies. This starts from the preparation stage, the implementation of activities. After PKM was carried out on breastfeeding mothers on July 02, 2021. The results showed that mothers felt more understanding and enjoyed the process of breastfeeding their babies so that the baby felt safe and comfortable in giving breast milk, this was shown by the babies becoming calmer and more relaxed. rest comfortably.